Should I Change Anticoagulane in Veno-Venous ECMO? - Rabia Yılmaz; Murat Arslan; Deniz Özel Bilgi; Zafer Çukurova (Turkish Journal of Anaesthesiology and Reanimation, 2025)
Objective: Due to a lack of high-quality data to guide anticoagulation therapy in extracorporeal membrane oxygenation (ECMO) patients, there is significant variation in practice among centers. We aimed to investigate the safety, anticoagulation efficacy, and cost-effectiveness of using bivaluridine as a primary anticoagulant without unfractionated heparin (UFH) in ECMO patients. Methods: The study population included patients undergoing Veno-Venous ECMO for acute respiratory distress syndrome. A total of 56 patients were evaluated, 25 were on UFH and 31 were on bivalirudin. Results: There was no significant difference between the time to reach the target activated partial thromboplastin time (aPTT) interval [6 (3.5-11) UFH, 9 (4-19) bivalirudin, P=0.287]. There was no significant difference between the percentage of time spent in the target aPTT interval (61.48±14.72 UFH, 62.65±11.99 bivaluridine, P=0.745). The median amount of erythrocyte suspension replacement (12.04±8.01; 7.9±4.71; P=0.028) and the median amount of fresh frozen plasma replacement [4 (2-6); 1 (0-4); P=0.001] were higher in the UFH group than in the bivaluridine group. The cost was lower in the UFH group compared to the bivalirudin group [$38.1 (13.5-48.7); $463.7 (194.3-819.8); P < 0.001]. Conclusion: The use of bivaluridine as a primary anticoagulant does not lead to any decrease in anticoagulant efficacy.